Graphene additive effects on diesel blend fuels for performance, combustion and emissions on diesel engine - Wan Muhammad Noor Sarbani, Mat Daud (2022)
The trend of global warming and greenhouse emissions remains as is for the foreseeable future, despite the advancements made in alternative fuels. The burning of fossil fuels in the internal combustion engines of private cars, commercial vehicles, and other modes of transportation is the primary source of emissions. Various ways can reduce emissions, such as reducing vehicle weight, using alternative energy sources, and adding additives to the fuels. Researchers have performed a few studies to study the effects of graphene nanoplatelets' application as an additive in diesel engines. This research aims to analyse the physicochemical properties of the diesel-graphene mixture and to evaluate the effect of performance and emissions of diesel-graphene blends in a single cylinder CI engine. Furthermore, this research aims to predict the effect of performance and emissions of diesel-graphene blends in a compression ignition engine through analytical and computational methods. In this research, the physicochemical properties of the dieselgraphene blends (density, viscosity, and calorific value) were tested using ASTM standards. The properties are then compared to fuel diesel, which was used as the baseline in this study. The stability of the blends was also tested using visual observation and UVVis spectroscopy. The fuel blends were then run in a single-cylinder diesel engine. The engine was run with five different speeds (900, 1200, 1500, 1800, and 2100) rpm, six different loads (0, 20, 40, 60, 80, and 100) %, and five different blends (0, 25, 50, 75, and 100) ppm. The experiment results were analysed with basic statistics, bar charts, and scatterplots. Minitab® is the tool chosen to produce the prediction model. The response surface methodology is applied in producing the prediction model. Surface and contour plots were used to simulate the predicted values. The results from the property tests showed that the addition of graphene nanoplatelets increased the viscosity and density of the diesel. However, the calorific value of the blends is found to be lower than pure diesel. The results from the experiments indicated improvement in brake torque, brake power, brake specific fuel consumption, and brake thermal efficiency at high loads (80% - 100%). Moreover, the emission of CO2 and NOx have been reduced at all different loads. However, the emission of CO was only reduced at high loads (100%) but increased at lower loads. The prediction model using response surface methodology for all parameters (Torque, Power, BSFC, and BTE) has been established. All the models showed good agreement compared with the experimental data (less than ±10%). In addition, a prediction model for all emission parameters (CO, CO2, and NOx) have been established. All the models showed good agreement compared with the experimental data (less than ±10%), except the prediction model for CO did not show good agreement due to the fact this is diesel engine emission- which reflects CO value to be extremely low and even negligible. In conclusion, this research has successfully determined the effects of graphene nanoplatelets on the physicochemical properties of diesel-graphene blends. The experiments also successfully demonstrated the effects of diesel-graphene blends on the performance and emissions of a single-cylinder compression ignition engine. Additionally, this study also managed to produce a realistic prediction model for the effects of graphene nanoplatelets usage as an additive to diesel engine performance and emissions.